Disordered cutaneous microbiota in systemic lupus erythematosus. Issue 108 (March 2020) - Huang, Cancan; Yi, Xiaoqing; Long, Hai; Zhang, Guiying; Wu, Haijing; Zhao, Ming; Lu, Qianjin
Abstract: The correlation between systemic lupus erythematosus (SLE) and microbiota colonization has been receiving much attention during recent years. Here, we screened the cutaneous bacterial spectrums of 69 SLE patients, 49 healthy controls and 20 dermatomyositis (DM) patients and identified the specific changes of cutaneous microbial composition and abundance in SLE patients. We observed the decreasing diversity in community richness and evenness and the greater heterogeneity in SLE patients compared to healthy controls, which were also different from the cutaneous microbiome of DM patients. The skin microbial community disorders in SLE patients were correlated with several clinical features such as serum low complement level, gender, renal involvement and myositis. According to the Kruskal-Wallis (KW) test, receiver operating characteristic (ROC) curve and LDA Effect Size (LEfSe) analysis, several bacterial taxa such as Staphylococcus, especially Staphylococcus aureus and Staphylococcus epidermidis, were identified to be potential markers for SLE skin lesions. Furthermore, Picrust analysis showed that Staphylococcus aureus infection pathway was significantly enriched and exhibited a strong correlation with genus Staphylococcus in SLE patients. The changes in the composition and abundance of cutaneous microbiota in SLE patients suggest that the microbial dysbiosis is associated with the pathogenesis of SLE, which may be potentially reliable biomarker or therapeutic target for SLE. Highlights: SLE cutaneous microbiota exhibited decreased alpha-diversity and increased heterogeneity compared with healthy controls. SLE skin exhibited increased abundances of Staphylococcus and Corynebacterium1, and decreased abundance of Cutibacterium . The skin microbial community disorders in SLE patients were correlated with several clinical features. There were 11 different predictive functional pathways of microbial community between SLE patients and healthy controls. S.aureus and S.epidermidis could be potential biomarkers for SLE diagnosis with high distinguishing accuracy.